Evaluation of T2 Magnetic Resonance (T2MR®) Technology for the Early Detection of ESKAPEc Pathogens in Septic Patients - Celestino Bonura; Domenico Graceffa; Salvatore Distefano; Simona De Grazia; Oscar Guzman; Brian Bohn; Mariachiara Ippolito; Salvatore Campanella; Angelica Ancona; Marta Caputo; Pietro Mirasola; Cesira Palmeri; et al. (MDPI AG, 2024)
Bloodstream infections (BSIs) and sepsis are a major cause of morbidity and mortality. Appropriate early antibiotic therapy is crucial for improving the survival of patients with sepsis and septic shock. T2 magnetic resonance (T2MR®) technology may enable fast and sensitive detection of ESKAPEc pathogens directly from whole-blood samples. We aimed to evaluate concordance between the T2Bacteria® Panel and standard blood culture and its impact on antibiotic therapy decisions. We conducted a single-centre retrospective study on patients with sepsis-induced hypotension or septic shock admitted to general, post-operative/neurosurgical, and cardiothoracic Intensive Care Units who were tested with the T2Bacteria® Panel from January 2021 to December 2022. Eighty-five consecutively admitted patients were included, for a total of 85 paired tests. A total of 48 ESKAPEc pathogens were identified by the T2Bacteria® Panel. The concordance rate between the T2Bacteria® Panel and blood cultures was 81% (69/85), with 20 concordant-positive and 49 concordant-negative cases. For the 25 microorganisms grown from accompanying blood cultures, blood pathogen coverage by the T2Bacteria® Panel was 88%. In this cohort of severely ill septic patients, the T2Bacteria® Panel was highly concordant and was able to detect more ESKAPEc pathogens, with a significantly shorter turn-around time compared to conventional blood cultures. The T2Bacteria® Panel also significantly impacted decisions on antibiotic therapy.